Anaphylactic Reaction Rates to Blue Dyes Used for Sentinel Lymph Node Mapping: Systematic Review and Meta-analysis. Issue 6 (June 2021) - Perenyei, Miklos; Barber, Zoe E.; Gibson, John; Hemington-Gorse, Sarah; Dobbs, Thomas D.
Abstract : Objective: The primary objective of this study was to quantify the risk of anaphylaxis to blue dyes used in SLNB for cancer. Secondary outcomes included the identification of factors that may influence this risk. Summary of Background Data: Blue dyes are widely used to help identify sentinel lymph nodes in oncological surgery. The rate of severe allergic reactions to blue dyes remains a controversial topic, with the true incidence and influencing factors uncertain. Methods: A systematic review and meta-analysis was performed to identify all studies which report on the incidence of severe adverse reactions and anaphylaxis to blue dyes (patent blue, isosulfan blue, methylene blue, and indigo carmine), when used for SLNB. Collected data included cancer and dye type, volume, and method of injection. Incidence was estimated using the arcsine method of statistical analysis. Results: One hundred nine studies documenting 94 episodes of anaphylaxis in a total of 61, 951 SLNB procedures, resulting in a weighed anaphylaxis rate of 0.061%. SLNB for breast cancer carries an anaphylaxis risk of 0.083%, with the risk markedly lower in melanoma surgery (0.0043%). Low dye volume (<2 mL) and intradermal injection are both associated with lower rates of anaphylaxis (0.031% and 0.0068%). Isosulfan blue seems to be the most anaphylactogenic amongst blue dyes with a rate of 0.16%. There were no reported cases of death in this cohort. Conclusion: Anaphylaxis to blue dyes in SLNB is rare. Methylene blue, patent blue, lower dye volumes, and intradermal administration are all associated with a lower incidence of anaphylaxis. Abstract : Supplemental Digital Content is available in the text